Research on subject behavior choice of marine carbon sink projects under risk conditions - He, Yixiong; Wang, Yanwei (Frontiers in Marine Science, 2024)
Marine carbon sink projects are important carriers for the development and utilization of marine carbon sink resources. The risk factors existing in the development process of marine carbon sink projects will significantly affect the behavior of the project subject, and then affect whether or not the project development can be conducted smoothly. Based on the evolutionary game method, this paper analyzes the behavior choice of each project subject under the risk condition, and explores the influencing factors that promote the change of its action probability. The results show that: (1) Government subsidies can promote the development of marine carbon sink projects, but when the subsidies are too large, the government's willingness decreases, which may lead to significant changes in the decisions of relevant practitioners; (2) The government pays more attention to image improvement, is not sensitive to risks, and always chooses active subsidies. In the case that the risk poses a great threat to the project, the behavior strategies of the relevant practitioners and investors will influence each other, and both sides will determine the behavior strategies that can obtain more returns according to the other side's behavior decision; (3) The behavior of relevant practitioners and investors has an impact on the strategy of the demander. When the risk increases, the former has a greater impact on the demander's choice not to buy marine carbon sink. Relevant policy suggestions are put forward: (1) the government should flexibly adjust the subsidy mechanism; (2) enhance the influence and popularity of marine carbon sink projects; (3) reduce the risks faced by the practitioners.